Practice pattern of use of high sensitivity troponin in the outpatient settings. Issue 12 (22nd October 2020) - Ferro, Enrico G.; Bhatt, Ankeet S.; Zhou, Guohai; Fiumara, Karen; Wasfy, Jason H.; Sequist, Thomas D.; Morrow, David A.; Scirica, Benjamin M.
Abstract: Background: High‐sensitivity troponin assays (hs‐Tn) detect lower serum concentrations than prior‐generation assays and help guide acute coronary syndrome (ACS) evaluation in emergency departments. Outpatient hs‐Tn utilization is not well described. Hypothesis: Outpatient providers use hs‐TnT to triage patients with suspected ACS. Methods: We compared the volume of outpatient prior‐generation troponin tests in the pre‐hsTn implementation period (January 2015‐March 2018) with outpatient hs‐TnT volume in the post‐implementation period (April 2018‐January 2020). Triage patterns were compared between patients with hs‐TnT≥99th vs <99th percentile, using two‐sample t tests. In patients triaged home, adverse events were compared between patients with hs‐TnT≥99th vs <99th percentile, using log‐rank tests. Results: Across a large tertiary healthcare system, a mean of 80 prior‐generation tests/month were ordered during the pre‐hsTn implementation period compared with 12 hs‐TnT tests/month in the post‐implementation period. Prior‐generation orders rose by 1.72 tests/month during pre‐implementation, vs a decline of 2.74 hs‐TnT tests/month during post‐implementation ( P < .001). Among 129 hs‐TnT orders, most were placed by cardiologists (54%) and primary care providers (32%). Patient symptoms at the time of troponin ordering included dyspnea (34%) and chest pain (33%), although 25% were asymptomatic. Among symptomatic patients (n = 74), those with hs‐TnT > 99th percentile were more likely to be sent to the ED (RR, 3.36; 95% CI, 1.22‐9.25; P = .002). Among patients sent home (n = 66), those with hs‐TnT > 99th percentile had more adverse events by 6 months (3.3% vs 22.2% RR, 6.67; 95% CI, 1.04‐42.9; P = .026). Conclusions: In this healthcare system, outpatient troponin utilization significantly declined since hs‐TnT implementation. Some providers use hs‐TnT to triage patients with suspected ACS to the ED; others test asymptomatic patients and some send patients home despite high hs‐TnT values.